2014
DOI: 10.17221/64/2012-pps
|View full text |Cite
|
Sign up to set email alerts
|

Effects of buprofezin and imidacloprid on the functional response of Eretmocerus mundus Mercet

Abstract: Sohrabi F.,Shishehbor P., Saber M., Mosaddegh M.S. (2014): Effects of buprofezin and imidacloprid on the functional response of Eretmocerus mundus Mercet. Plant Protect. Sci., 50: 145-150.Eretmocerus mundus Mercet is one of the key natural enemies of bemisia tabaci (Gennadius). In this study, the sublethal effects of LC 25 of imidacloprid and field-recommended concentration of buprofezin on the functional response of E. mundus to different densities of second instar b. tabaci nymphs were evaluated. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
(21 reference statements)
2
8
0
1
Order By: Relevance
“…: Braconidae) (Abedi et al, 2012, Mahdavi et al, 2013, Rashidi et al, 2018, Dolichogenidea tasmanica (Cameron, 1912) (Hym. : Braconidae) (Paull et al, 2014), and Eretmocerus mundus Mercet, 1931 (Sohrabi et al, 2014) have been reported in previous studies. Nevertheless, there is no available information on the sublethal effects of insecticides on A. bambawalei.…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…: Braconidae) (Abedi et al, 2012, Mahdavi et al, 2013, Rashidi et al, 2018, Dolichogenidea tasmanica (Cameron, 1912) (Hym. : Braconidae) (Paull et al, 2014), and Eretmocerus mundus Mercet, 1931 (Sohrabi et al, 2014) have been reported in previous studies. Nevertheless, there is no available information on the sublethal effects of insecticides on A. bambawalei.…”
Section: Introductionsupporting
confidence: 70%
“…In another study, the type of functional response of Diaretiella rapae (McIntosh) did not change when it was exposed to primicarb and thiamethoxam (Rezaei et al, 2014). However, Sohrabi et al (2014) reported an alteration in type III functional response of Eretmocerus mundus Mercet in control treatment as well as imidacloprid to type II in buprofezin treatment. Moreover, the sublethal concentrations of primicarb, cypermethrin, and dimethoate changed the functional response of D. rapae from type II to type III (De-Jiu et al, 1991).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…It has been observed that not only the mites are affected by the application of sublethal doses or pesticides residues, other organisms commonly used for the biological control are also exposed to changes in their demographic behavior and the functional response (Stark et al, 2004;Talebi et al, 2008, Sohrabi et al, 2014. In this case, mites exposed to sublethal concentrations did not show a change in their functional response, but positive in its efficiency (Table 1; Figure 1).…”
Section: Resultsmentioning
confidence: 94%
“…Se ha observado efectos sobre depredadores como en la sobrevivencia de adultos de Chrysoperla carnea (Stephens, 1836) (Rogers, Krischik & Martin, 2007) y sobre Orius insidiosus (Say, 1832) (Funderburk, Srivastava, Funderbuck & McManus, 2013). Se ha determinados los efectos toxicológicos del imidacloprid en parasitoides como Eretmocerus mundus (Mercet, 1931) (Sohrabi, Shishehbor, Saber & Mosaddegh, 2014), Habrobracon hebetor Say, 1857 (Sarmadi, Nouri-Ganbalani, Rafiee-Dastjerdi, Hassanpour & Farshbaf-Pourabad, 2010;Rafiee-Dastjerdi et al, 2012) y Microplitis croceipes (Cresson, 1872) (Stapel, Cortesero & Lewis, 2000). De igual forma se han visto efectos deletéreos del imidacloprid sobre hongos antagonistas como Trichoderma harzianum (Rifai, 1969;Sivparsad, Chiuraise,Laing & Morris, 2014).…”
Section: Discussionunclassified